(untitled) (Research, Society and Development, 2021)
Gestational syphilis, despite being characterized as a preventable disease with available treatment, persists with high rates of transmission, despite the increased coverage of care to pregnant women and newborns. In order to seek a better understanding of this phenomenon, this study seeks to map the international scientific production on gestational syphilis associated with mother-to-child transmission. This is an exploratory, descriptive study based on the bibliometric analysis of the scientific production published in the Web of Science database. Data analysis was carried out using the HistCiteTM software. After applying the refinement filters, 121 articles were identified, published in 79 different journals. These were written by 720 authors with links to 339 institutions, located in 53 countries. A total of 3,201 references were used, an average of 26 references per article. It was observed that in recent years there has been, in Brazil and worldwide, a positive impact on indicators related to gestational and congenital syphilis, but there is evidence of failures in prenatal care that culminate in the vertical transmission of syphilis and consequently the non-eradication of congenital syphilis as expected in pacts and global goals.